2021
DOI: 10.1038/s42003-021-02422-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the world’s smallest flowering plant, Wolffia australiana, helps explain its specialized physiology and unique morphology

Abstract: Watermeal, Wolffia australiana, is the smallest known flowering monocot and is rich in protein. Despite its great potential as a biotech crop, basic research on Wolffia is in its infancy. Here, we generated the reference genome of a species of watermeal, W. australiana, and identified the genome-wide features that may contribute to its atypical anatomy and physiology, including the absence of roots, adaxial stomata development, and anaerobic life as a turion. In addition, we found evidence of extensive genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…Effective vegetative propagation increases biomass production rate, and cloning maintains genetic uniformity facilitating industrial applications. So far, only one genome has been sequenced (W. australiana) [36,37] further comparison among chloroplast genomes shows that the genus Wolffia possesses the most reduced genome size in Lemnaceae [38]. Genome size varied between 375 Mb in W. australiana to 1881 Mb in W. arrhiza [39].…”
Section: Plant Morphological and Reproductive Traitsmentioning
confidence: 99%
“…Effective vegetative propagation increases biomass production rate, and cloning maintains genetic uniformity facilitating industrial applications. So far, only one genome has been sequenced (W. australiana) [36,37] further comparison among chloroplast genomes shows that the genus Wolffia possesses the most reduced genome size in Lemnaceae [38]. Genome size varied between 375 Mb in W. australiana to 1881 Mb in W. arrhiza [39].…”
Section: Plant Morphological and Reproductive Traitsmentioning
confidence: 99%
“…We also identified homozygous single nucleotide polymorphism (SNP) sites and insertion/deletion (InDels) by comparing the genome sequence reported here with those from other W. australiana species, yielding 6,764 SNPs and 3,166 InDels with minimal support of at least five Illumina reads (Dataset, Table S6). The contig N50 of our Waus genome was 18,579,918 bp compared to 251,357 bp for wa7733, 102,226 bp for wa8730, and 742,788 bp for wa8730 (three other published W. australiana genomes) (16,17). Analysis of Benchmarking Universal Single-Copy Orthologs (BUSCO) demonstrated that our genome assembly is much more complete than previously sequenced and assembled W. australiana genomes, with BUSCO scores of 94.55% (Waus), 77.10% (wa7733), 80.29% (wa8730), and 87% (wa8730) (Table 1; Dataset, Table S7).…”
Section: Resultsmentioning
confidence: 86%
“…Here, we report our efforts in developing W. australiana as a model system. We sequenced the genome of this species, which will complement other genome sequences from this species recently published (16, 17) and set up a “Plant-on-Chip (PoC)” culture system with which to observe morphological characteristics, particularly in the diploid phase. We also exploited the genomic information we generated to analyze the possible mechanisms behind unique morphological traits seen in W. australiana such as the lack of a root or a vasculature and the fast transition from vegetative to reproductive growth.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of SpGARP (35) and WaGARP genes (28) were less than those of A. thaliana (56), C. esculenta (46), O. sativa (56), which was consistent with previous report of WRKY TF family in aquatic plants. The reason may be related to the minimal gene set of duckweed genomes (18,708 genes in S. polyrhiza, and about 15,000 genes in W. australiana ) [ 25 , 54 , 55 ]. However, S. polyrhiza had more IId members than C. esculenta , O. sativa and W. australiana , suggesting that NIGT1 subfamily underwent expansion in the adapting to various aquatic environments.…”
Section: Discussionmentioning
confidence: 99%